Asuhan Kebidanan Komprehensif Pada Ny. I Umur 32 Tahun Dengan Grande Multipara Dan Kurang Energi Kronik Di Puskesmas Bumiayu Tahun 2023 - Thania Alfi Gina Insani; Endang Susilowati; Khunelis Khunelis (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
High parity pregnancies increase the risk of complications for both the mother and fetus. In the Bumiayu Community Health Center alone in 2021-2022 there were 45 cases of mother with grande multipara. To provide Comprehensive Midwifery Care service to pregnant, maternity, newborn, postpartum and family planing sevices in a comprehensif manner though a midwifery management approach according to Varney and SOAP. Based on the bacground above, the problem formulation is how to provide comprehensive midwifery care for Mrs. I aged 32 years in the Bumiayu Community Health Center, Brebes Regency in 2022. The author uses a quality descriptive research method with a case study approach. In pregnancy cases of anemia and CED were found, partus precipitatus birth accurred. As well as giving formula milk to babies and lack of personal hygiene in neonatus and the normal postpartum periode. Grande Multipara Comprehensive Midwifery Care, Presipitatus delivery, giving formula milk to babies, and lack of personal hygiene with newborn and normal postpartum bebies.